Perancangan Sistem Proxy Server Menggunakan Protokol WCCPv2 dengan Konfigurasi Multi Router - Fatah Mumtaz Al'Ala; Rinta Kridalukmana; Eko Didik Widianto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
Numbers of internet users are increasing incredibly fast. Ideally, this increasing numbers of users are also supported by capacity uplift, in this case an increase in bandwidth to maintain the standard services that received by the users. However, increasing the bandwidth not always becomes the first option since it is quite expensive. Implementing proxy server as content/cache engine is the other option available. It will cache the content that user requested and keep it for a while for servicing the other users that will request the same content in the future. WCCP protocol is used to redirect user’s traffic to the proxy server. The standard proxy server configurations are using single router with one or more proxy servers. This thesis is aims to design and implement proxy server system with multi routers configuration. Multi routers configuration is used as a failover mechanism to provide network high availability. It will use HSRP protocol to provide the high availability services. Tests that conducted after implementation shows the increase in transaction and successful transaction by 296% and 284% also a decrease in response time as well as failed transaction by 18% and 99% consecutively. Failover test shows the percentage of packet loss amounted to 31,3% and 26,3% for clients in VLAN 10 and VLAN 20 consecutively. The average time required for clients to reconnect to the internet after router failure is 7 seconds for clients in VLAN 10 and 6 seconds for client in VLAN 20.